The Psychology of Trust - Peaslee Levine, Martha (IntechOpen, 2023)
Trust has always been complicated. This book works to examine aspects and theories of trust. Chapters look at trust in the workplace. It considers types of leadership and how that influences the trust of employees. As workplaces and societies become more diverse, there can be an impact on trust. Many times, individuals will have implicit biases that can influence their perception of others and their ability to trust. Trust has also become more complicated with the advent of the internet. We can now connect with more ideas and individuals. Yet, is the person who communicates back with us real? Is it someone with a fake account or maybe not even a person at all, but a robot? Even though trust is complicated and we can sometimes be taken advantage of, we still need to find ways to trust others in our lives. Trust allows us to develop a community. We have always needed the community to be safe, both physically and emotionally. This book allows you to connect with new ideas and aspects of trust.